Redescription of Pinnixa haematosticta Sakai, 1934, its transfer to Indopinnixa Manning & Morton, 1987, and a reappraisal of Indopinnixa kumejima Naruse & Maenosono, 2012 (Decapoda: Brachyura: Pinnotheridae) - Komai, Tomoyuki; Naruse, Tohru; Yokooka, Hiroyuki; Taru, Masanori; Shimetsugu, Miho; Watanabe, Tetsuya (Zootaxa, 2022)
The poorly known pinnotherid crab, Pinnixa haematosticta Sakai, 1934, is redescribed on the basis of female holotype and additional specimens, including males and females, from Japan. The male characters of the species are documented for the first time. The species is transferred to Indopinnixa Manning & Morton, 1987 because the male pleonal somites 3–5 are functionally fused, the telson is wide, and the maxilliped 3 with the dactylus is distinctly longer than the propodus. Indopinnixa kumejima Naruse & Maenosono, 2012 is morphologically very similar to I. haematosticta n. comb., but a molecular phylogenetic analysis using partial fragments of the mitochondrial 16S rRNA gene supports the hypothesis that the two taxa as distinct. Morphologically, the two species are differentiated by the shape of the pereopod 4 merus (proportionally wider in I. haematosticta n. comb. than in I. kumejima). Our findings suggest that I. haematosticta n. comb. and I. kumejima are geographically distinct: I. haematosticta appears restricted to the Japanese mainland (Honshu to Kyushu) and Ohsumi Islands, while I. kumejima occurs in the Ryukyu and Ogasawara Islands.